Autonomous Wristband Placement in a Moving Hand for Victims in Search and Rescue Scenarios With a Mobile Manipulator. - Pastor-Martín, Francisco; Ruiz-Ruiz, Francisco Jesús; Gómez-de-Gabriel, Jesús Manuel; García-Cerezo, Alfonso José (My University, 2023)
In this letter, we present an autonomous method for the placement of a sensorized wristband to victims in a Search-And-Rescue (SAR) scenario. For this purpose, an all-terrain mobile robot includes a mobile manipulator, which End-Effector (EE) is equipped with a detachable sensorized wristband. The wristband consists of two links with a shared shaft and a spring. This configuration allows the wristband to maintain fixed to the EE while moving and get placed around the victim’s forearm once the contact is produced. The method has two differentiated phases: i) The visual moving hand tracking phase, where a 3D vision system detects the victim’s hand pose. At the same time, the robotic manipulator tracks it with a Model Predictive Controller (MPC). ii) The haptic force-controlled phase, where the wristband gets placed around the victim’s forearm controlling the forces exerted. The wristband design is also discussed, considering the magnitude of the force needed for the attachment and the torque the wristband exerts to the forearm. Two experiments are carried out, one in the laboratory to evaluate the performance of the method and the second one in a SAR scenario, with the robotic manipulator integrated with the all-terrain mobile robot. Results show a 97.4% success in the wristband placement procedure and a good performance of the whole system in a large scale disaster exercise
Keywords: Robótica; Ayuda en las catástrofes; Robots autónomos; Robotics